Correlation between estrogen and alkaline phosphatase expression in osteoporotic rat model - Sherman Salim (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Osteoporosis is a systemic disease that can decrease bone density as a result of imbalance bone remodeling and bone resorption. Estrogen reduction due to menopause can increase osteoclast activity and furthermore decrease bone density. Estrogen can stimulate alkaline phosphatase (ALP) expression, collagen type I and osteocalcin in bone remodelling process. Ovariectomized rat is a common animal for studying patofisiology, diagnosis and treatment osteoporosis patient. Purpose: To evaluate correlation between estrogen and ALP expression in osteoporotic rat model mandible. Methode: 18 female wistar rats, 2 months old, 200 grams were divided into 2 groups, ovariectomized group and sham surgery as control group. Surgery was done under intra muskular anesthesia using combination 2% xylazine 1cc and 10% ketamine 1cc. After 12 weeks, mandible was taken for ALP examination and blood from heart was taken to evaluate the amount of estrogen. Result: There was significant correlation between estrogen and ALP expression in osteoporotic rat model mandible. Conclusion: The amount of estrogen can influence ALP expression activity.